2014
DOI: 10.1179/1743281214y.0000000209
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study of phase transitions and mechanism of reduction of FeO from high Ti-bearing blast furnace primary slag by graphite

Abstract: The reduction of FeO from iron-saturated FeO-CaO-SiO 2 -MgO-Al 2 O 3 -TiO 2 slags by graphite has been studied under static conditions between 1473 and 1623 K. The results show that the Fe/Ti mole ratio in the sample matrix decreases with increasing time and temperature. Most of the FeO was reduced within the first 10 min at 1573 K. The degree of reduction was found to increase rapidly with increasing temperature below 1573 K and was controlled not only by the effective diffusivity of CO and FeO concentration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…4 The reaction conditions of the experiments for all samples are given in Table 2. Each sample was placed in a graphite crucible and introduced from the bottom of the vertical tube furnace and suspended by the platinum wire.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The reaction conditions of the experiments for all samples are given in Table 2. Each sample was placed in a graphite crucible and introduced from the bottom of the vertical tube furnace and suspended by the platinum wire.…”
Section: Methodsmentioning
confidence: 99%
“…4 The slag was pre-melted, quenched, crushed and ground. 1-3 mass-% B 2 O 3 was then added (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the final slag, the slag system formed in the lower part of the BF, which is composed of primary slag and bosh slag, has distinct characteristics and different slag behavior [5][6][7][8][9], which has not been fully elucidated to date. In the BF process, it is generally believed that the BF primary slag has more research significance than the final slag [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research [9][10][11][12][13][14][15][16], Ti-bearing ore sintering and Ti-bearing slag characteristics were studied systematically. B 2 O 3 was chosen as the modifier for obtaining the Ti-rich phases, and the results showed that the rise of the (Mg + Al)/(Ca + Si) ratio and B 2 O 3 in slag were beneficial to form [TiO 6 ] 8− octahedral units and thus beneficial to the precipitation of anosovite from the TBBF slag [14,15].…”
Section: Introductionmentioning
confidence: 99%